Characterization of an Extracellular Virulence Factor Made by Group A Streptococcus with Homology to the Listeria monocytogenes Internalin Family of Proteins - Reid, Sean D. (American Society for Microbiology, 2003)
Leucine-rich repeats (LRR) characterize a diverse array of proteins and function to provide a versatile framework for protein-protein interactions. Importantly, each of the bacterial LRR proteins that have been well described, including those of Listeria monocytogenes, Yersinia pestis, and Shigella flexneri, have been implicated in virulence. Here we describe an 87.4-kDa group A Streptococcus (GAS) protein (designated Slr, for streptococcal leucine-rich) containing 10 1/2 sequential units of a 22-amino-acid C-terminal LRR homologous to the LRR of the L. monocytogenes internalin family of proteins. In addition to the LRR domain, slr encodes a gram-positive signal secretion sequence characteristic of a lipoprotein and a putative N-terminal domain with a repeated histidine triad motif (HxxHxH). Real-time reverse transcriptase PCR assays indicated that slr is transcribed abundantly in vitro in the exponential phase of growth. Flow cytometry confirmed that Slr was attached to the GAS cell surface. Western immunoblot analysis of sera obtained from 80 patients with invasive infections, noninvasive soft tissue infections, pharyngitis, and rheumatic fever indicated that Slr is produced in vivo. An isogenic mutant strain lacking slr was significantly less virulent in an intraperitoneal mouse model of GAS infection and was significantly more susceptible to phagocytosis by human polymorphonuclear leukocytes. These studies characterize the first GAS LRR protein as an extracellular virulence factor that contributes to pathogenesis and may participate in evasion of the innate host defense.